Spin-phonon coupling in uniaxial anisotropic spin-glass based on Fe2TiO5 pseudobrookite - Rodrigues, João E.F.S. (2019)
The ferric pseudobrookite is a rare example of uniaxial anisotropic spin-glass insulator, depicting a multiglass behavior and magnetoelectric coupling. Here, we present Raman spectroscopy results in order to elucidate the spin-phonon coupling in Fe2TiO5 for the first time. The experimental data are supported by computational simulations performed in view of density functional theory, which allowed us to assign the main Raman-active modes. Temperature-dependent phonon behavior exhibited anomalous evolution around 55 and 80–200 K, which was explained as successive coupling between lattice and spin configuration arising from spin freezing and short-range magnetic correlation, respectively. Arguments that the magnetoelectric effect in Fe2TiO5 is mediated by spin-phonon coupling are presented.